2020
DOI: 10.1016/j.ekir.2020.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for Patients With COVID-19 and Acute Kidney Injury: A Systematic Review and Meta-Analysis

Abstract: Introduction: There are limited data on the association of kidney dysfunction with prognosis in coronavirus disease 2019 (COVID-19), and the extent to which acute kidney injury (AKI) predisposes patients to severe illness and inferior outcomes is unclear. We aim to assess the incidence of AKI among patients with COVID-19 and examine their associations with patient outcomes as reported in the available literature thus far. Methods: We systematically searched MEDLINE, EMBASE, SCOPUS, and MedRxiv databases for fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
209
1
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(238 citation statements)
references
References 43 publications
(58 reference statements)
16
209
1
12
Order By: Relevance
“…While causality cannot be inferred from an observational study, the uremic milieu caused by AKI can impact immune function,27 inflammation,28 and coagulation 29. Consistent with our findings, recent publications have reported on the association of AKI with inhospital death among those hospitalized with COVID-1911 . Early reports from Wuhan, China, found that even after adjusting for age, sex, disease severity, and comorbid conditions, the risk of death was increased with AKI (HR ranging 1.9-4.7 for increasing stages of AKI).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…While causality cannot be inferred from an observational study, the uremic milieu caused by AKI can impact immune function,27 inflammation,28 and coagulation 29. Consistent with our findings, recent publications have reported on the association of AKI with inhospital death among those hospitalized with COVID-1911 . Early reports from Wuhan, China, found that even after adjusting for age, sex, disease severity, and comorbid conditions, the risk of death was increased with AKI (HR ranging 1.9-4.7 for increasing stages of AKI).…”
supporting
confidence: 90%
“…where large numbers of patients did not have completed outcomes, 7,11,37 over 99% of our patients had completed outcomes, with fewer than 1% still hospitalized. We employed time-toevent analyses using AKI exposure as a time-varying covariate, and thus avoiding immortal time bias.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 86%
See 1 more Smart Citation
“…Although far from detailed, the importance of AKI has been more profiled by several reports in COVID-19 patients (6, 7). More recently, several meta-analyses have proved the important prognostic values of AKI in severe COVID-19 patients (74)(75)(76)(77). As a vital complication, the presence of AKI was associated with more adverse prognosis in the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of renal replacement therapy and renal recovery before and during the COVID-19 pandemic-A single centre observational study Introduction Provision of renal replacement therapy (RRT) for patients with COVID-19 was challenging for both logistical and disease-related factors [1]. A signi cant proportion of COVID-19 patients developed acute kidney injury (AKI), many of whom require RRT [2]. In our institution, as with many others, shortages of continuous venovenous hemodia ltration (CVVHDF) machines and replacement uids necessitated reduced intensity of hemo ltration (exchange rates) to facilitate the greatly increased demand for RRT capacity.…”
mentioning
confidence: 99%